The Next Decade : Empire and Republic in a Changing World - Friedmam, George (GHQ, Rawalpindi Army Publishing House, 2012)
Focusing on the most pressing global issues of 2010, George Friedman takes an eye-opening look at what the next ten years has in store. From Islam's decline to China's financial crisis, Friedman offers a number of scenarios and predictions.
Include Maps
Keywords: Military policy -- War